Driving without wings: the effect of different digital mirror locations on the visual behaviour, performance and opinions of drivers - Large, David; Crundall, Elizabeth; Burnett, Gary; Harvey, Catherine; Konstantopoulos, Panos (Elsevier, 2016)
Drivers' awareness of the rearward road scene is critical when contemplating or executing lane-change manoeuvres, such as overtaking. Preliminary investigations have speculated on the use of rear-facing cameras to relay images to displays mounted inside the car to create ‘digital mirrors'. These may overcome many of the limitations associated with traditional ‘wing’ and rear-view mirrors, yet will inevitably effect drivers' normal visual scanning behaviour, and may force them to consider the rearward road scene from an unfamiliar perspective that is incongruent with their mental model of the outside world. We describe a study conducted within a medium-fidelity simulator aiming to explore the visual behaviour, driving performance and opinions of drivers while using internally located digital mirrors during different overtaking manoeuvres. Using a generic UK motorway scenario, thirty-eight experienced drivers conducted overtaking manoeuvres using each of five different layouts of digital mirrors with varying degrees of ‘real-world’ mapping. The results showed reductions in decision time for lane changes and eyes-off road time while using the digital mirrors, when compared with baseline traditional reflective mirrors, suggesting that digital displays may enable drivers to more rapidly pick up the salient information from the rearward road scene. Subjectively, drivers preferred configurations that most closely matched existing mirror locations, where aspects of real-world mapping were largely preserved. The research highlights important human factors issues that require further investigation prior to further development/implementation of digital mirrors within vehicles. Future work should also aim to validate findings within real-world on-road environments whilst considering the effects of digital mirrors on other important visual behaviour characteristics, such as depth perception.